Pengaruh Range of Motion (ROM) terhadap Kekuatan Otot pada Pasien Stroke - Susanti Susanti; Susanti Susanti; Difran Nobel BIstara (Jurnal Kesehatan Vokasional, 2019)
Background: The weakness muscle is the biggest impact on patients with stroke, to the practice Range Of Motion with the aim is to maintain or preserve muscle strength, to maintain mobility joints and simulate circulation. With an increase in the incidence of stroke and disability, if the practice Range Of Motion is not implemented it will be a significant decrease in muscle strength, cause muscle kontraktur and a decubitus. Objective: The study aims to find his Range of Motion of muscle strength in patients with stroke in the Puskesmas Bulak Banteng Surabaya. Methods: This study uses Pra-eksperimental One Grup Pra-Post Test Design. Population in this study is a stroke patient who live in the Puskesmas Bulak Banteng Surabaya and sampels 32 of responden. The sample by using techniques simple random sampling. Variables independent in this study is Range Of Motion and the variables dependent is muscle strength. The instrument used in the collection of data is an observation to the strength of muscle and Range of Motion. Result: Wilcoxon test results show the significance level p value = 0.00 with α = 0.05 (p <α) on the right hand while in the left hand shows a significant level p value = 0.00 with α = 0.02 (p<α ).Conclusion:  H0 is rejected that there is influence between ROM exercises gripping the ball against the muscle tone in the right hand and left hand that suffered a stroke.Keywords: Range Of Motion, muscle strength.